Immune response of the chicken in determination of virulence profiles of Salmonella enterica - Setta, Ahmed Mohamed Hassanin (2011)
Salmonella enterica subspecies enterica (S. enterica) infection remains a global problem in a wide range of animals and in man. Poultry-derived food is a common source of human infection with the non-host-adapted Salmonella strains while fowl typhoid and pullorum disease are serious diseases in poultry. Development of novel immune-based control strategies against Salmonella infection necessitates a better understanding of the host-pathogen interactions at the cellular level. This study characterizes, in vitro and in vivo, the immune responses that develop following infection of avian species with typhoid and non-typhoid Salmonella serotypes. Salmonella serovars Typhimurium, Enteritidis, Hadar and Infantis showed a greater level of invasion and/or uptake characters to both chicken macrophages (HD11) and chicken kidney epithelial cells (CKC), when compared with S. Pullorum or S. Gallinarum. Nitrate and reactive oxygen species were greater in Salmonella-infected HD11 cells compared with the non-infected controls. HD11 cells revealed higher mRNA gene expression for CXCLi2 (IL-8), IL-6 and iNOS genes in response to S. Enteritidis infection when compared to S. Pullorum-infected cells. S. Typhimurium- and S. Hadar-infected HD11 showed higher gene expression for CXCLi2 versus S. Pullorum-infected cells. Higher mRNA gene expression levels of pro-inflammatory cytokine IL-6, chemokines CXCLi1 (K60) and CXCLi2 and iNOS genes were detected in S. Typhimurium- and S. Enteritidis-infected CKC followed by S. Hadar and S. Infantis while no significant changes were observed in S. Pullorum or S. Gallinarum-infected CKC. Epithelial cell response and production of pro-inflammatory cytokines and chemokines were greatly influenced by Salmonella virulence markers, including Salmonella pathogenicity island type-1 (SPI-1), SPI-2 and bacterial flagella. In chicken infections, S. Enteritidis and S. Infantis colonized the caeca more efficiently than S. Gallinarum and S. Pullorum. High numbers of B-lymphocytes and macrophages were observed in the caecal tonsils of infected birds. S. Enteritidis infection in newly hatched birds elicited the expression of CXCLi1 and CXCLi2 chemokines in the caecal tonsils, while S. Gallinarum up-regulated the expression of LITAF. In older chickens, S. Enteritidis infection resulted in a significantly higher expression of CXCLi2, iNOS, LITAF and IL-10 while S. Pullorum appeared to down-regulate CXCLi1 expression in the caecal tonsils. Data from spleens showed either no expression or down-regulation of the tested genes. In conclusion, data from the present study provide further insights on the interaction of Salmonella with poultry, and while both S. Typhimurium and S. Enteritidis are strong inflammatory serotypes, S. Pullorum and S. Gallinarum are not.